Hak Perempuan dan Hukum Perceraian Islam: Antara Otonomi Agama dan Perlindungan Minoritas - Utami, Adelya Putri; Rodliyah, Nunung; Tamza, Fristia Berdian; S, Sepriyadi Adhan; Kasmawati, Kasmawati (Muqaranah, 2025)
The application of Islamic divorce law in societies that adhere to legal pluralism presents unique challenges, particularly in the context of protecting women's rights when the Muslim community is a minority. In a number of countries, Islamic family law is still used as an internal guideline for Muslim communities in resolving divorce and property division issues. However, this practice often conflicts with human rights principles, particularly those related to gender equality. This study aims to analyze how pluralistic countries balance respect for religious freedom with the state's obligation to protect individual rights. The research methodology used is a qualitative approach with normative and comparative juridical methods, through analysis of legislation, court decisions, and legal literature in the United Kingdom, India, and Indonesia. The study results indicate that the protection of women's rights should not be compromised in the name of cultural tolerance or religious autonomy. The state has a crucial role to ensure that the application of religious law is fair, voluntary, and transparent, and in line with the principles of justice and equality for all citizens.